The effect of tax awareness, tax socialization, tax service quality, and tax digitalization on tax compliance among Micro, Small, and Medium Enterprises (MSMEs) - Nicholas Ananda Setyawan; Bagas Johantri (Educoretax, 2026)
This study aims to examine the influence of tax awareness, tax socialization, tax service quality, and tax digitalization on tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Sleman Regency. As one of the key drivers of the national economy, MSMEs play a crucial role in economic growth; however, their tax compliance level remains relatively low, as reflected in the limited submission of Annual Tax Returns (SPT). Employing a quantitative approach, this research utilizes a survey method by distributing questionnaires to MSME taxpayers registered at the Sleman Primary Tax Office (KPP Pratama Sleman), with the collected data analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) through SmartPLS 4 software. The results demonstrate that tax awareness, tax socialization, tax service quality, and tax digitalization have a positive and significant effect on tax compliance, implying that better understanding of tax obligations, effective dissemination of taxation information, high-quality public services, and the integration of digital technology in taxation systems can significantly enhance the compliance of MSME taxpayers. These findings highlight the importance of strengthening both conventional and digital strategies within tax administration, suggesting that policymakers and tax authorities should prioritize not only increasing awareness and service quality but also accelerating digital transformation to foster a more effective and sustainable tax compliance environment.